(untitled) (REMUNOM, 2026)
Understanding pastoral suicide requires looking beyond social factors to include institutional pressures, inner conflicts, and existential dimensions inherent to ministry. Pastoral suffering is shaped by such pressures and existential demands specific to the pastoral role. Phenomenology provides a framework for grasping the phenomenon by focusing on pastors’ ways of being and unveiling their lived experience. Objective: This study aimed to examine, through an integrative review, the scientific literature on suicide among pastors. Methodology: An integrative review inspired by PRISMA was conducted, guided by the question: “What has the scientific literature produced about pastoral suicide?” Searches in SciELO, BVS LILACS, PubMed MEDLINE, Scopus, Web of Science, and PsycINFO resulted in a corpus of four articles addressing the topic. The analysis followed a phenomenological-hermeneutic approach. Results and Discussion: The four studies reveal that the pastoral mode of being-in-the-world is marked by loneliness, overload, and silencing. Religion can increase risk by fostering guilt, shame, and stigma, or serve as protection by rearticulating meaning after crisis. Dysfunctional leadership conflicts and institutional instability intensify stress and vulnerability. Providing emotional support to the congregation may itself predict suicidal ideation. Pastoral suicide emerges when possibilities of meaning and action are obscured, constituting a limit experience. Final Considerations: The topic remains underexplored, particularly in Portuguese-language research. There is an urgent need for an ethic of “care for the caregiver,” creating spaces for clinical and pastoral supervision, reflecting on sustainable workloads, and strengthening mental health support networks within religious contexts.